ANALYSIS AND METHODS OF THE PECULIARITIES OF PERCEPTION, MEMORIZATION AND COMPARISON OF THE AMOUNT OF OBJECTS IN PRESCHOOL CHILDREN - Toshmatova Zamiraxon Jumanovna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article describes the analysis and methods of the peculiarities of the perception, memorization and comparison of the amount of objects in preschool children.